An Analysis of Divestiture Effects Resulting from Deregulation - CHEN, ANDREW H.; MERVILLE, LARRY J. (Journal of Finance, 1986)
ABSTRACT Capital market data were used to examine the divestiture effects pertaining to deregulation, the dropping of antitrust charges, and the reversing of the co‐insurance effect associated with the recent breakup of AT&T. The empirical results of the study indicate that significant economic events took place during the breakup process, which led to transfers of wealth from various parties to the securityholders of AT&T. The results also indicate that the buffering effect of regulation was reduced as AT&T went through the total deregulation process. This is in accordance with Peltzman's prediction.